Study of Marriage Age Limit According to Indonesian Marriage Law - Nurul Miqat; Susilawati, Susi; Korompot, Ratu Ratna; Mubarak, Ayyub; Ikbal, Mohammad (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Indonesia is a country that is blessed with being a pluralistic nation, consisting of several tribes, religions, and cultures. For this reason, the recognition of customary law is also recognized as long as it still exists, and the implementation of marriages is also according to customary law, which is in accordance with the customary law of each region. The research method uses normative research. The findings showed that the age of the prospective groom was 19 years and that of the prospective bride was 16 years. After the amendment, there are no differences. These age limits for marriage are a measure of the maturity of persons who want to marry, carried out by people who have not reached the age of marriage.